2010
DOI: 10.1002/bdra.20656
|View full text |Cite
|
Sign up to set email alerts
|

Cleft lip and palate results from Hedgehog signaling antagonism in the mouse: Phenotypic characterization and clinical implications

Abstract: Background-The Hedgehog (Hh) pathway provides inductive signals critical for developmental patterning of the brain and face. In humans as well as in animal model systems, interference with this pathway yields birth defects; among the most well-studied of which fall within the holoprosencephaly (HPE) spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 54 publications
3
77
0
2
Order By: Relevance
“…8N,O,T,U). It is established that abnormally low and high levels of Shh can also result in facial abnormalities (Lipinski et al, 2010), and the improved phenotype observed further supports the notion that the increased Shh level observed in Hand1 phospho-mutants contributes directly to the mid-face cleft phenotype.…”
Section: Inhibition Of Shh Signaling Partially Rescues Hand1 Phosphomsupporting
confidence: 58%
“…8N,O,T,U). It is established that abnormally low and high levels of Shh can also result in facial abnormalities (Lipinski et al, 2010), and the improved phenotype observed further supports the notion that the increased Shh level observed in Hand1 phospho-mutants contributes directly to the mid-face cleft phenotype.…”
Section: Inhibition Of Shh Signaling Partially Rescues Hand1 Phosphomsupporting
confidence: 58%
“…Specifically, secretion of SHH ligand from the ectoderm activates pathway activity in the adjacent cranial neural crest-derived mesenchyme (Marcucio et al, 2005;Hu and Marcucio, 2009;Hu et al, 2015;Xavier et al, 2016). Demonstrating clinical relevance, we have shown that transient in utero exposure to the Shh pathway inhibitor cyclopamine causes lateral clefts of the lip that typically extend into the primary and secondary palate, and that this model recapitulates human non-syndromic cleft lip with or without cleft palate (CL/P) (Lipinski et al, 2008b(Lipinski et al, , 2010(Lipinski et al, , 2014. Here, we utilized this pathway-specific mouse model of cleft lip to identify and investigate the mechanism of action of Shh target genes that mediate normal and abnormal upper lip morphogenesis.…”
Section: Introductionmentioning
confidence: 61%
“…This subcutaneous infusion exposure model yields steady-state serum concentrations within a few hours after pump implantation (GD8.25) that persist until dispensation is complete (∌GD9.375) (Lipinski et al, 2008b(Lipinski et al, , 2010.…”
Section: Cyclopamine Administrationmentioning
confidence: 99%
“…Finally, the anterior and intermediate lobes of the pituitary gland derive from the oral ectodermal placode, while the posterior pituitary is derived from the neural ectoderm. A recent study in mice showed that anterior pituitary is indeed majorly affected in those with orofacial clefts (34). To act on this knowledge, the type and severity of orofacial clefts may be considered to be parallel to the accompanying pituitary defects.…”
Section: Discussionmentioning
confidence: 99%